Validity and Reliability of Elasticity Multiple-Choice Items (EMCI) Using Rasch Model - Mardian, Vivi; Samsudin, Achmad; Utama, Judhistira Aria; Suwarma, Irma Rahma; Coştu, Bayram (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
Assessment in the form of an instrument is very important to test for validity and reliability so that it can measure student learning outcomes. We implemented a measurement instrument designed to assess students' understanding of elasticity. The measurement instrument consisted of 15 items. The instrument was administered to students who were taking physics subjects in senior high school in their second year. In total, 74 students were taken from two classes in Padang, Indonesia. In this study, the students' performance was collected as quantitative data and evaluated using the Rasch model. The results showed that the data matched the Rasch model measurements. Moreover, female students answered 53 percent of the questions better than male students. Furthermore, the DIF plot shows that S8 is the most difficult problem, while S14 is the easiest. There are two gender bias questions, namely S12 and S14. Both questions were easily solved by female students. However, all questions can be used to measure students' abilities in elasticity and Hooke's law. This study seeks to make a contribution to the literature on EMCI evaluations by offering a case study for academics and researchers to use in assessing students' elasticity skills